Sexual Assault and the Association With Health, Quality of Life, and Self-Efficacy in the General Norwegian Population. Issue 3 (February 2022) - Schou-Bredal, Inger; Bonsaksen, Tore; Ekeberg, Øivind; Skogstad, Laila; Grimholt, Tine K.; Lerdal, Anners; Heir, Trond
The lifetime prevalence of sexual assault was examined in a representative sample of the general Norwegian adult population ( n  = 1, 792), in addition to the association between sexual assault and health, quality of life, and general self-efficacy. Respondents completed questionnaires assessing these factors. Overall, 6.7% ( n  = 120) of the respondents (10.9% of women and 1.9% of men) reported an experience of sexual assault. Respondents in the sexual assault group reported significantly worse mental and physical health as well as poorer quality of life and lower self-efficacy, compared with those without sexual assault experience. The most prevalent mental problems in the sexual assault group were depression (61.7%), sleep problems (58.3%), eating disorders (26.7%), and posttraumatic stress disorder symptoms at a clinical level (25.0%). The most prevalent physical problems were chronic pain (47.5%) and musculoskeletal disease (30.8%). The proportions of physical and mental health problems were not significantly different between male and female victims. Results indicated that having experienced sexual assault during one's life appears to be associated with lifetime occurrence of multiple health problems for both genders and reduces a person's perceived general self-efficacy and quality of life.